Una retrospezione intelettuale - F. HAHN (Moneta e Credito, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. Rather than provide an autobiographical sketch, however, Frank Hahn concentrates on his journeyings through economic history. In doing so, the author hopes to stimulate readers to look at their own intellectual journey and reflect on it.